Contaminación de moscas domesticas con Salmonella - Arenas Mosquera, David José; Joaquim, Patricia Estefania; Riera, Nicolas Iván; Young, Brian Jonathan; Socas, Maria Laura; Balbiani, Facundo; Chacana, Pablo (Asociación Latinoamericana de Avicultura, 2024)
Poster